Answer:
B and F
Step-by-step explanation:
Given
x² + 4x + 4 = 12 ( subtract 4 from both sides )
x² + 4x = 8
Using the method of completing the square to solve for x
add ( half the coefficient of the x- term )² to both sides
x² + 2(2)x + 4 = 8 + 4, that is
(x + 2)² = 12 ( take the square root of both sides )
x + 2 = ± [tex]\sqrt{12}[/tex] ( subtract 2 from both sides )
x = ± [tex]\sqrt{12}[/tex] - 2
= ± 2[tex]\sqrt{3}[/tex] - 2
Hence
x = 2[tex]\sqrt{3}[/tex] - 2 → B
x = - 2[tex]\sqrt{3}[/tex] - 2 → F